Teoria do dano concentrado aplicada ao cálculo da flecha imediata em vigas de concreto armado - Souza, Adysson André Fortuna de (2019)
The deflection evaluation in beams is a fundamental step for structural design development, which aims to estimate the behavior of the structure in service situation. In this step, is analyzed the largest axis bent displacement for the structural element. In a reinforced concrete beam, this displacement has a nonlinear behavior, and to better describe it, a nonlinear structure analysis method is required. Currently, some standards adopt the Branson Formula or the Bilinear Method that use an effect weighting between Stages I and II in an attempt to specify the immediate deflection in reinforced concrete beams. However, both calculation methods are a linear structural analysis method. Although, this study proposes a new alternative for quantifying deflection in reinforced concrete beams using the Lumped Damage Mechanics. This is a nonlinear analysis method using concepts of fracture mechanics and damage mechanics coupled with plastic hinges. The accuracy of the developed formula was verified through comparisons with experimental works developed by other authors, as well as comparing with the Branson Formula, the Bischoff Method which is an adaptation of the Branson Formula, and the Bilinear Method. The results showed that the proposed procedure needs modifications in order to better describe the mechanical behavior of the beams analyzed in Stage II.